2017
DOI: 10.1093/icvts/ivx230
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of postinfarction ventricular septal defect: risk factors and outcome analysis

Abstract: Surgical repair of postinfarction ventricular septal defect has a high 30-day mortality rate. Higher age at presentation and postoperative renal replacement therapy are independent predictors of early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
6
10
2
Order By: Relevance
“…Similarly to previous reports, we found that patients undergoing surgery temporarily closer to the index MI were more likely to die 7,10–12 . Immediately after the MI, tissues are more friable, and this makes the operation more technically demanding.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to previous reports, we found that patients undergoing surgery temporarily closer to the index MI were more likely to die 7,10–12 . Immediately after the MI, tissues are more friable, and this makes the operation more technically demanding.…”
Section: Discussionsupporting
confidence: 86%
“…. The data obtained are consistent with the literature report on the high risk of death in patients with post-MI VSD during surgery at the early stages after the development of acute MI, against the hemodynamic instability and comorbidity [8,13,14,15], and CKD as an early mortality risk factor [16].…”
Section: Resultssupporting
confidence: 91%
“…A significant limitation to this study is that we were unable to separate concomitant CABG procedures by bypassed territory. Surgeons in the concomitant CABG are separated into two camps: those who argue any stenotic vessels that are not supplying infarcted tissue should be grafted 17 and those who argue grafting to infarcted vessels is beneficial in reperfusing the ischemic border and preventing ventricular arrhythmias 18 . Since we cannot separate these data, it is not possible to say which technique is superior.…”
Section: Discussionmentioning
confidence: 99%
“…those who argue any stenotic vessels that are not supplying infarcted tissue should be grafted 17 and those who argue grafting to infarcted vessels is beneficial in reperfusing the ischemic border and preventing ventricular arrhythmias. 18 Since we cannot separate these data, it is not possible to say which technique is superior. Given a mean follow up of 2.06 years, it is also possible that the benefits of CABG have not been significantly demonstrated in this cohort as most benefits to CABG are seen following a 24 month period.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%